Решите уравнение методом введения новой неизвестной[latex]( \frac{ x^{2} +x}{3} -2)( \frac{ x^{2} +x}{2} -2)-( \frac{ x^{2} +x}{3}-1)( \frac{ x^{2} +x}{2} +6 )=-9[/latex]
Решите уравнение методом введения новой неизвестной
[latex]( \frac{ x^{2} +x}{3} -2)( \frac{ x^{2} +x}{2} -2)-( \frac{ x^{2} +x}{3}-1)( \frac{ x^{2} +x}{2} +6 )=-9[/latex]
Ответ(ы) на вопрос:
х²+х=у
(у/2-2)(у/3-2)-(у/3-1)(у/2+6)=-9
((у-6)/3)((у-4)/2)-((у-3)/3)((у+12)/2)=-9
(у²-6у-4у+24)/6-(у²-3у-36+12у)/6=-9
у²-10у+24-у²-9у+36=-54
-19у=-54-24-36
-19у=-114
у=6
х²+х=6
х²+х-6=0
х₁,₂=-1₊⁻√(1+24) = -1⁺₋5
2 2
х₁=2 х₂=-3
Не нашли ответ?
Похожие вопросы